2022
DOI: 10.25105/jet.v2i2.14903
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Sustainability Awareness Terhadap Kinerja Keuangan Dan Nilai Perusahaan Di Sektor Pertanian 2016-2020

Abstract: Penelitian ini bertujuan untuk menguji pengaruh Sustainablity Awareness terhadap Kinerja Keuangan dan Nilai Perusahaan pada perusahaan di sektor pertanian. Lahan pertanian mengambil alih sepertiga dari total luas lahan Indonesia, karena itu pertanian berpotensi menjadi sumber pendapatan utama bagi sebagian besar warga negara. Akibat pesatnya pertumbuhan industri ini, kerusakan hutan tropis dan perubahan iklim semakin parah, kerusakan ekologi dan bahaya bagi fauna dan flaura, hilangnya keanekaragaman hayati, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…This theory supports the author's assumption that the high value of OPM will encourage companies to use internal funding to finance production and operations to increase the output of goods or services. The ESG aspect has not been a major consideration for companies in Indonesia in increasing company value (Nurfahmi & Anis, 2022). This finding is in line with the results of previous research, which showed that OPM has no s ignificant influence on the stock prices of banking companies on the Indonesian Stock Exchange (Choiriyah et.al, 2021).…”
Section: Variablessupporting
confidence: 84%
“…This theory supports the author's assumption that the high value of OPM will encourage companies to use internal funding to finance production and operations to increase the output of goods or services. The ESG aspect has not been a major consideration for companies in Indonesia in increasing company value (Nurfahmi & Anis, 2022). This finding is in line with the results of previous research, which showed that OPM has no s ignificant influence on the stock prices of banking companies on the Indonesian Stock Exchange (Choiriyah et.al, 2021).…”
Section: Variablessupporting
confidence: 84%
“…Menurut (Freeman, 1984;Aras et al, (2018b), menunjukkan bahwa membangun hubungan yang kuat dengan multi pemangku kepentingan memungkinkan akan tercapainya sebuah tujuan. Bhattacharya dan Sharma (2019) menyatakan bahwa pertimbangan pemangku kepentingan utama menjadi dasar bagi perusahaan untuk melakukan pelaporan CSR (Nurfahmi & Anis, 2019).…”
Section: Tinjauan Pustakaunclassified